Comparison of glenohumeral and humerothoracical range of motion in healthy controls, osteoarthritic patients and patients after total shoulder arthroplasty performing different activities of daily living - Bruttel, Hendrik; Spranz, David Maximilian; Bülhoff, Matthias; Aljohani, Nasser; Wolf, Sebastian Immanuel; Maier, Michael Wolfgang (Gait & posture, 2019)
Purpose - The purpose of this study was to examine how total shoulder arthroplasty improves performance of activities of daily living compared to patients with glenohumeral osteoarthritis and how they perform compared to healthy controls. - Methods - Glenohumeral and humerothoracical elevation used by patients with primary osteoarthritis (12 participants, 16 shoulders), after total shoulder arthroplasty (16 participants, 24 shoulders) and healthy controls (11 participants, 22 shoulders) for four different activities of daily living were assessed using 3D motion analysis. Analysis of range of motion and angle time series was performed. - Results - Range of motion used for activities of daily living was better in patients treated with anatomical total shoulder arthroplasty than in patients with primary glenohumeral osteoarthritis. Although it was still reduced compared to healthy individuals. Angle time series showed improved kinematics in patients with total shoulder arthroplasty compared to patients with glenohumeral osteoarthritis. Both glenohumeral and humerothoracical elevation kinematic time series were in almost all cases in between the control group’s and the osteoarthritis group’s. - Conclusion - Total shoulder arthroplasty improves performance of activities of daily living in patients with primary glenohumeral osteoarthritis but cannot restore the full range of Motion compared to healthy controls. A prospective study with pre- and postoperative examinations is necessary to understand to understand how preoperative status influences the postoperative results.